Reproduction Policy in the Twenty-First Century: A Comparative Analysis - Hannah Zagel (Edward Elgar Publishing, 2024)
This pertinent book investigates how governments are involved in human reproduction. Adopting a multidisciplinary approach, the book provides crucial insights from the fields of sociology, law, political science and demography to better understand reproduction policy in the twenty-first century.
Additional information: Förderhinweis: "This is an Open Access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on ElgarOnline, thanks to generous funding support from the WZB Berlin Social Science Center and the Leibniz Open Access Monograph Publishing Fund."
Keywords: 320; welfare state; reproductive rights; reproductive autonomy; reproductive governance; pronatalism; comparative methods